2017
DOI: 10.1021/acscentsci.6b00361
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of (+)-Ryanodine and (+)-20-Deoxyspiganthine

Abstract: (+)-Ryanodine is a natural product modulator of ryanodine receptors, important intracellular calcium ion channels that play a critical role in signal transduction leading to muscle movement and synaptic transmission. Chemical derivatization of (+)-ryanodine has demonstrated that certain peripheral structural modifications can alter its pharmacology, and that the pyrrole-2-carboxylate ester is critical for high affinity binding to ryanodine receptors. However, the structural variation of available ryanodine ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Although several electrochemical approaches were reported for similar intramolecular couplings of aromatic imines and esters, few have been explored on the corresponding aliphatic system, especially a complex aliphatic system that contains multiple continuous stereocenters. As a category of powerful reductants involving single-electron processes, lithium-arenides were employed in some challenging C–C bond formations. , Due to the uncertainty of the reductive C–C coupling between an aliphatic imine and an ester, metal–arene-based conditions were chosen by us as a feasible starting point for the examination. Lithium naphthalenide was first examined, but unfortunately the desired spiro -α-aminocyclopentanone 26 was not observed (Table , entry 1).…”
supporting
confidence: 82%
“…Although several electrochemical approaches were reported for similar intramolecular couplings of aromatic imines and esters, few have been explored on the corresponding aliphatic system, especially a complex aliphatic system that contains multiple continuous stereocenters. As a category of powerful reductants involving single-electron processes, lithium-arenides were employed in some challenging C–C bond formations. , Due to the uncertainty of the reductive C–C coupling between an aliphatic imine and an ester, metal–arene-based conditions were chosen by us as a feasible starting point for the examination. Lithium naphthalenide was first examined, but unfortunately the desired spiro -α-aminocyclopentanone 26 was not observed (Table , entry 1).…”
supporting
confidence: 82%
“…The use of VO(On-Pr)3 61 proved essential to obtain full conversion of alkene 42; the more routinely used VO(acac)2 gave only 5-10% conversion under otherwise identical conditions. Treatment of epoxylactone 43 with LiDBB, 62 the optimal conditions from our (+)-ryanodine synthesis, 25 did produce small quantities of the desired pentacycle 46; however, significant decomposition was observed. Analysis of the side products revealed that reduction of the orthobenzoate was a competing process, prompting a screen of different reductants in order to prevent this undesired reactivity.…”
mentioning
confidence: 87%
“…In a subsequent study, Reisman discovered that a key intermediate from the ryanodol synthesis could be esterified to incorporate the pyrrole-3-carboxylate ester directly, allowing the total synthesis of ryanodine in only 18 steps from (S)-pulegone. 10 Reisman's synthetic platform uniquely positions her group to develop synthetic ryanoids that were simply inaccessible through semi-synthesis.…”
mentioning
confidence: 99%